2021
DOI: 10.3390/atmos12030378
|View full text |Cite
|
Sign up to set email alerts
|

Loading Rates of Dust and Bioburden in Dwellings in an Inland City of Southern Europe

Abstract: Sampling campaigns indoors have shown that occupants exposed to contaminated air generally exhibit diverse health outcomes. This study intends to assess the deposition rates of total settleable dust and bioburden in the indoor air of dwellings onto quartz fiber filters and electrostatic dust collectors (EDCs), respectively. EDC extracts were inoculated onto malt extract agar (MEA) and dichloran glycerol (DG18) agar-based media used for fungal contamination characterization, while tryptic soy agar (TSA) was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 65 publications
(122 reference statements)
0
9
0
Order By: Relevance
“…Previous studies also identified passive sampling as suitable to determine Aspergillus section Fumigati by culture-based methods through sampling of filtering respiratory protective devices and other environmental matrices in settings such as waste-sorting plants, veterinary clinics, dairies, ambulances, and many other indoor and occupational environments [4,10,16,18,32]. In fact, passive sampling is able to characterize contamination levels over a wider period of time, compared to air sampling [21,36]. Thus, higher fungal counts and greater fungal diversity are expected by passive sampling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies also identified passive sampling as suitable to determine Aspergillus section Fumigati by culture-based methods through sampling of filtering respiratory protective devices and other environmental matrices in settings such as waste-sorting plants, veterinary clinics, dairies, ambulances, and many other indoor and occupational environments [4,10,16,18,32]. In fact, passive sampling is able to characterize contamination levels over a wider period of time, compared to air sampling [21,36]. Thus, higher fungal counts and greater fungal diversity are expected by passive sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus section Fumigati was more frequent in DG18 compared to MEA counts. Despite the recommendation of using MEA for aerobiological studies in a Portuguese regulatory framework dedicated to the assessment of indoor air quality (IAQ) (25APA 2010), DG18 is an efficient option due to its restrictive character, inhibiting the development of fastidious fungal species [21]. The results of some fungal overgrowth on the MEA plates may have influenced the development of Aspergillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sampling method is appropriate for large-scale epidemiological studies intending to measure microbial exposure, and to complement exposure information collected by building inspections dedicated to spotting dampness and mold [ 3 , 4 ]. EDC is also being used to assess microbial contamination using molecular tools as stand-alone analyses [ 4 , 5 , 6 , 7 , 8 ], even the most refined ones such as sequencing [ 2 ], or using side by side, culture-dependent, and independent methods [ 3 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In fact, the use of qPCR analyses from EDC is a promising tool to accurately measure microbial contamination in dwellings [ 4 , 8 , 24 ].…”
Section: Introductionmentioning
confidence: 99%